Media directory. (Diplomatic Post Pub., 1989)
"The 1995 Media Directory of the Philippines was prompted by an urgent need by business government and public relations executives and candidates. It also seek to provide a useful guide for Filipinos and foreigners who wish to network with Filipinos residing in the Philippines and in other countries. The directory contains addresses and details of different media in the Philippines whether it be in print or in the radio. A list of media people located outside the country are contained in this directory. It also includes the photos and resumes of media leaders in the Philippines."